Strengthening the Students’ Social-Emotional Competence to Prevent Vulnerability as Victims and Perpetrators of Bullying - Susanto (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities through strengthening social emotional competence to prevent the vulnerability of elementary school students as victims and perpetrators of bullying aim to raise awareness of the importance of preventing bullying both as victims and perpetrators. Community service methods through socialization, education and role playing. Data collection techniques through observation, interviews and document studies. Data analysis using the Miles and Huberman technique. The program was implemented in three stages: preparation, implementation, monitoring, and evaluation. First, the preparation stage involved observing students in school, identifying issues, and determining the appropriate forms of intervention. In addition, the implementation stage included strengthening socio-emotional competencies tailored to students’ developmental stages. The next was the monitoring and evaluation stage. It assessed the students’ understanding and evaluated the overall process of the program. The results revealed significant improvements: responsible decision-making increased by 95%, relation skills by 92%, social awareness by 90%, and self-management by 87%. Furthermore, the participants also expressed positive feedback. It deals with the clarity of material delivery, the use of media and supporting tools, and the engaging methods during the program.